(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Consumer Food security, personal wellness, and ecological issues, as well as sensual aspects like nutritious value, flavor, cleanliness, and beauty, all impact natural agricultural choices. While ethnic considerations may aid in the identification of organic clients, the link isn’t very strong. Customers link organic food with organic procedures, ecological and livestock health, and the lack of pesticides and fertilizers. High costs continues to restrict organic product use. Knowing the elements that influence natural foods intake, such as motivations, is critical to assessing if clean product has the capacity to become a truly mainstream market. Agricultural security, human wellness, and environmental issues, as well as senses aspects such as nutritious value, flavor, fresh, and beauty, all affect customer preference for organic foods. While demographic considerations may aid in the identification of organic clients, the link isn’t very strong. Consumers link organic food with organic procedures, environmentalist and animal health, and the lack of herbicides and fertilizers. High costs continue to restrict organic food use. Understanding the elements that influence natural product intake, such as desire, is important, is important to determining if organic food has the potential to become a true mainstream industry.